Results of experimental studies of stem raw material chopper - Bratishko, V.; Milko, Dmytro; Мілько, Дмитро Олександрович; Милько, Дмитрий Александрович; Kuzmenko, V.; Achkevych, O. (My University, 2021)
Chopping of stem crops is one of the main operations in feed preparation technologies and biofuel production. We have proposed the design of a chopper of stem plant raw materials with a horizontal rotor, which combines in one working chamber two stages of chopping. Using the developed chopper, experimental studies of the process of chopping stem crops were carried out. The aim of the experimental studies was to establish the influence of the chopping process parameters (cutting speed, raw material supply, and the number of counter cuts) on the efficiency indicators - specific energy consumption and average particle size. The parameter of the number of counter cuts characterizes the intensity of the chopping process and is proportional to the number of crossing of the cutting pairs in one turn of the rotor. The raw material for chopping was a mixture of legumes with a predominance of alfalfa with a moisture content of 12.9%. When conducting the research, the limits of variation of factors were: the cutting speed – 36.19-54.29 m·s-1, raw material supply – 0.0167-0.0333 kg·s-1, the number of counter cuts – 21-49 pieces. As a result of processing the obtained data, the dependences of the optimization criteria on the studied factors in the form of second-order polynomials were established. The coefficient of multiple determination for the model of specific energy consumption is D = 0.796819, for the average length of the chopped particles D = 0.857278. The coefficients of the models are significant at the confidence level of at least 94%. Depending on the values of the studied parameters, the specific energy consumption for the chopping process varied from 4.00 to 15.83 kWh·t-1, the average length of the chopped particles - from 3.43 to 6.04 mm. Experimental studies have proved the possibility of establishing the optimal values of the parameters of the chopping process for a given length of particles of stem raw materials.
Keywords: stem plant bioresources; specific energy consumption; chopper; cutting speed